Mutations within the decoding site of Escherichia coli 16S rRNA: growth rate impairment, lethality and intragenic suppression. - Thomas, C L (1988)
Several C----U transitions and small deletions were introduced into the conserved region centered on base C1400 in Escherichia coli 16S rRNA by in vitro mutagenesis. The mutations were placed within rrnB operons on multicopy plasmids under the transcriptional regulation of either the normal rrnB P1P2 promoters or the temperature-inducible PL promoter from bacteriophage lambda and introduced into E. coli hosts. When expressed from the P1P2 promoters, several of the mutant 16S rRNAs impaired cell growth while others, including one in which U replaced C at position 1400 within the ribosomal decoding site, had little or no effect on cell doubling time. However, C----U transitions at positions 1395 and 1407, as well as the deletion of C1400, appeared to render their hosts inviable. Cells in which these mutations were expressed from the lambdaPL promoter died within four generations after induction. Unexpectedly, the lethal phenotype was suppressed intragenically by replacement of G1505 with A, C or U. Suppression may alleviate a functional defect in 30S subunits containing the U1395, U1407 or deltaC1400 mutations.